If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(-4a + -1) = 3(10a) Reorder the terms: 8(-1 + -4a) = 3(10a) (-1 * 8 + -4a * 8) = 3(10a) (-8 + -32a) = 3(10a) Remove parenthesis around (10a) -8 + -32a = 3 * 10a Multiply 3 * 10 -8 + -32a = 30a Solving -8 + -32a = 30a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-30a' to each side of the equation. -8 + -32a + -30a = 30a + -30a Combine like terms: -32a + -30a = -62a -8 + -62a = 30a + -30a Combine like terms: 30a + -30a = 0 -8 + -62a = 0 Add '8' to each side of the equation. -8 + 8 + -62a = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -62a = 0 + 8 -62a = 0 + 8 Combine like terms: 0 + 8 = 8 -62a = 8 Divide each side by '-62'. a = -0.1290322581 Simplifying a = -0.1290322581
| -11+5x-7+5=3+6x+x | | 5a-12=18 | | t+45=102 | | -5+2n=7n-5 | | 6q=-9+7q | | (1181*9491)/100 | | iz^2-2z^2=3 | | 1181*9491/100 | | 3/x=9/7 | | 2z/7-7=10 | | (X+15)+(x+10)=180 | | 25j^2+10j+1=0 | | 300=-0.005q^2+2.5q | | 9g=10g+6 | | .7d-15+d=2d-8-.4d | | l-3=9 | | 2(3x+4)=14-3(x-1) | | X^2-13y^2=-1 | | 7a^2x1/9= | | 20+20*0+1= | | 2x-3=-(4x-9) | | -4(9-f)=36 | | .42-.03c=33.3-c | | 2n+2.9=5.5 | | .2(12)+.5x=.1(12+x) | | x^2+9y^2=2 | | d^2+8d-33=0 | | 2x+12=-2x-(8) | | x^3-5x^2-9x+45= | | r=6(b+a) | | 1.02(1.23)(7-x)=8 | | 100/x-10=15 |